PHYTOCHEMICAL SCREENING, FTIR CHARACTERIZATION, AND ANTIMICROBIAL ACTIVITY OF DOUM PALM (HYPHAENE THEBAICA) - Ibrahim, Ibrahim Shuaibu; Birniwa, Abdullahi Haruna (FUDMA JOURNAL OF SCIENCES, 2024)
The doum palm fruit (Hyphaene thebaica), a native of northern Africa, is an oval, edible fruit that grows on desert palm trees. It grows extraordinarily well in the northern part of Nigeria as well. It is a member of the palm family Arecaceae. The optimal process for making an aqueous extract from raw doum fruit was determined using the extraction methods. The crushed doum fruit is soaked for 12 days at room temperature in a solution of methanol and ethanol. The plant's crude pericarp powder was used in the new study's phytochemical screening procedure using conventional phytochemical techniques. Tannins, carbohydrates, flavonoids, terpenes, and terpenoids were found in the extract in low and moderate concentrations, according to the phytochemical examination. To get high-spectral-resolution data over a broad spectral range, Fourier-transform infrared spectroscopy (FTIR) is utilized. Doum palm plants are a highly significant source of bioactive components that may be helpful in the creation of novel chemotherapeutic drugs. The results of FTIR analysis confirmed the presence of O-H, C-H, C=C, C=O, C-O, and C-H functional groups. The result shows the frequencies of 3268 cm-1,  2925 cm-1, 1719 cm-1, 1607 cm-1, 1443 cm-1 and 1287 cm-1  from Methanol extract and 3283 cm-1, 2925 cm-1, 1719 cm-1, 1611 cm-1, 1104 cm-1 and 992 cm-1 from Ethanol extract. The microbial activity of the doum palm fruit extract has shown a greater effect on Salmonella typhi and Escheria coli at high concentration of about both microbial organism but no effect at lower concentration of...
Keywords: Antimicrobial; Bioactive; FTIR; Phytochemicals